Plumage coloration, body condition and immunological status in Yellow-billed Cardinals (Paroaria capitata). Issue 4 (1st October 2016) - Dias, R.I.; Manica, L.T.; Gressler, D.; Bell, J.A.; Fecchio, A.
Abstract : Plumage coloration deriving from carotenoid and melanin pigments can be a quality signal in birds, and can be under conspecific inspection in social interactions. For example, parasite load and immune system status can be inferred through plumage color intensity, and can influence the choice of sexual partners. Here, we evaluated two plumage ornaments in the Yellow-billed Cardinal [ Paroaria capitata (d'Orbigny & Lafresnaye 1837)]: the carotenoid-based coloration of the cap and the melanin-based coloration of the bib. We evaluated whether these ornaments were related to blood parasite burden, immunological status and body condition, and whether they could reveal individual sex and age. Cardinals were mist-netted in a Brazilian wetland, and 12 individuals were infected with malaria parasites. Both carotenoid and melanin colorations were related to age, but only carotenoids reflected immunological status. Adult cardinals presented redder caps and darker bibs in comparison to juveniles, and redder caps were associated with low values of heterophil to lymphocyte ratio (H/L, indicating lower stress level). Plumage coloration did not indicate individual sex or parasite infection. Taken together, these results demonstrated that both melanin- and carotenoid-based coloration in cardinals can potentially reflect significant information for social interactions, such as individual age and experience, but apparently only carotenoid coloration is condition-dependent and could reliably indicate quality.